Enhancing the Seeking Safety group intervention with trauma-sensitive yoga practice: A program evaluation. (May 2019) - Murphy, Thomas M.; Dispenza, Franco; Chang, Catherine Y.; Elston, Nikki; Rumsey, Amanda; Sinclair, Moneta; Curtis-Davidson, Rico
Abstract: Background and purpose: The purpose of this article is to report the results of a qualitative Utilization Focused Program Evaluation on the integration of the Seeking Safety manualized group counseling intervention with Trauma-Sensitive (TS) yoga practice at a community mental health agency. To date, there has been no evaluation of Seeking Safety and TS yoga as complementary therapies. Method and materials: Qualitative data were generated from key informant interviews and focus groups, then coded and analyzed for theme and content. Results: Analysis of data indicate that, in this specific setting, the combination of Seeking Safety and TS Yoga was perceived by clients and clinicians as an effective complementary intervention strategy. Conclusion: The results of this qualitative evaluation are specific to the agency utilizing the interventions. By integrating Seeking Safety with TS yoga many of the inherent weaknesses of the two individual approaches were moderated. Highlights: Addiction and trauma are often co-occurring conditions. Seeking Safety is an evidence-based addiction intervention. Combining Trauma-Sensitive Yoga with Seeking Safety can increase effectiveness.